High-definition electro-anatomical mapping of Koch's Triangle including AV node potentials recordings in consecutive AVNRT patients. (19th May 2022) - Pandozi, C; Botto, GL; Del Giorno, G; Papa, AA; Castro, A; Di Belardino, N; Viani, S; Russo, M; Brasca, F; Carbone, A; Galeazzi, M; Casale, MC; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Activation mapping of Koch's Triangle, even when coupled with high density mapping, is incomplete without recordings of AV nodal electrical activity. Purpose: To identify, through a highly specific methodology and high-density electro-anatomical mapping (HDM), the slow AVN potential (AVNP) and the precise activation modality of Koch's Triangle in SR in atrio-ventricular nodal reentrant tachycardia (AVNRT) patients. Method: The 3D KT geometry was created from the Orion mapping and the Rhythmia Mapping System. KT was divided into 8 distinct regions moving from an antero-septal to postero-septal areas and bounded by tricuspid annulus (TA) anteriorly and tendon of Todaro posteriorly. AV nodal potential activity was recorded by non-standard bipolar electrogram filtering at 0.50–300 Hz. The AVNP was defined as a slow frequency potential between atrial and ventricular EGM similar to that reported by Scherlag and Jackman, and it was confirmed by high frequency atrial pacing. The AVNP was annotated at the end of electrogram when it was followed in the same recording by a sharp potential; otherwise it was annotated at the center. Data are reported as mean±SD. Results: Twenty successful SP ablation cases of typical AVNRT from 7 centers were included. RA acquired points during SR were 2512±1400 (123±67 acquired inside the KT, KT area of 41±64 mm2). The time of a complete RA mapping was 19.2±8 min. The AVNP was detected in all cases (n=20, 100%). At the mid-region of the KT, AVNP was identified in 20 (100%) cases; at postero-septal regions bounded anteriorly by the TA and posteriorly by the lateral wall toward the crista terminalis AVN was present in 17 (85%) cases; at mid-postero-septal regions AVN was detected in 15 (75%) cases. In all patients, the first activation in the KT was recorded in the antero-septal region at the expected site of the fast pathway; then the wavefront spread in two directions: anteriorly toward the His-bundle and posteriorly toward the base of KT colliding with the wavefront coming from the opposite direction through the slow pathway. In all patients, abolition of the SP and acute procedural success was achieved in the first procedure with 5.4±3 RF ablations. In 30 out 35 (86%) ablation sites, ablations were done at sites with concurrent detectable AVNP. No complications occurred. Conclusions: High-density mapping using a non-standard bipolar electrograms filtering at 0.50–300 Hz showed multiple electrograms in SR including low frequency potential that may represent the electrical activity of compact node and inferior extensions.